Assessment of Knowledge and Behaviour of Pharmacy Services Students in Vocational School Of Health Services for Rational Drug Use - Buyuker, Sultan Mehtap; Odabasi, Gamze (Eastern Journal of Medical Sciences, 2018)
Objective: To evaluate the knowledge and behaviour of the students about the rational drug use studying in the pharmacy services program in Vocational School of Health Services (VSHS). Methods: This cross-sectional study, conducted between 2017 October and 2018 March, was conducted on the first and second year students of a University VSHS Pharmacy Services Program. In this study, questionnaire was applied to 115 students to assess their knowledge and behaviour about the rational drug use. Results: The average age of the 115 students who participated in the study was 19.54±1.79 years. Among the causes of drug use by the participants, influenza (64.6%) was in the first place. Participants were asked to propose medication competence and 30.7% of the participants stated that they suggested prescribed drugs. The prominence of commercial advertising was questioned and 58.8% of the participants said they did not use the advertised products. Conclusion: In our study, it was seen that pharmacy technicians studying in pharmacy services program did not have sufficient knowledge about rational drug use. The content of training programs should include more information on rational drug use.